Accelerated Systemic Autoimmunity in the Absence of Somatic Hypermutation in 564Igi: A Mouse Model of Systemic Lupus with Knocked-In Heavy and Light Chain Genes - McDonald, Gabrielle; Medina, Carlos O.; Pilichowska, Monika; Kearney, John F.; Shinkura, Reiko; Selsing, Erik; Wortis, Henry H.; Honjo, Tasuku; Imanishi-Kari, Thereza (Frontiers in Immunology, 2017)
564Igi mice have knocked-in Ig heavy (H) and light (L) chain genes that encode an autoantibody recognizing RNA. Previously, we showed that these mice produce pathogenic IgG autoantibodies when activation-induced deaminase (AID) is expressed in pre-B and immature B cells but not when it is expressed only in mature B cells. AID has two functions; it is necessary for somatic hypermutation (SHM) and class switch recombination (CSR). To determine the role of each of these functions in the generation of pathogenic autoantibodies we generated 564Igi mice that carry a mutant AID-encoding gene, Aicda (AicdaG23S), which is capable of promoting CSR but not SHM. We found that 564Igi AicdaG23S mice secreted class-switched antibodies at levels approximately equal to 564Igi mice. However, compared to 564Igi mice, 564Igi AicdaG23S mice had increased pathogenic IgG antibodies and severe SLE-like disease, including, glomerulonephritis, and early death. We suggest that in 564Igi mice SHM by AID changes Ig receptors away from self-reactivity, thereby mitigating the production of autoantibody, providing a novel mechanism of tolerance.